MANAJEMEN KURIKULUM BERBASIS AKHLAK, NILAI, DAN MORAL DI PONDOK MODERN DARUSSALAM GONTOR - Aliva Erhan (STAI Ma'had Aly Al-Hikam Malang, 2020)
In the addition to the curriculum that is clearly written in the education program, Modern Islamic Boarding School Darussalam Gontor also implements a curriculum that relate to the transformation of student’s character, values, and morals. This curriculum is present in every student's social interaction and directly affect them. This paper discusses a curriculum based on character, values, and morals in Modern Islamic Boarding School Darussalam Gontor. Namely matters relating to the transformation of morals, values and morals of students at Modern Islamic Boarding School Darussalam Gontor and social interaction of moral and values based curriculum at Modern Islamic Boarding School Darussalam Gontor.